Synthesis, in situ spectroelectrochemistry and in situ electrocolorimetry of electrochromic octakis(chloroethylsulfanyl) phthalocyaninatomanganese(III) chloride - KOCA, ATIF (ROYAL SOC CHEMISTRY, 2009)
In this study, the syntheses of octakis(hydroxyethylsulfanyl) phthalocyaninatomanganese(III) chloride and its chlorinated derivative, octakis(chloroethylsulfanyl) phthalocyaninatomanganese(III) chloride, and successive electrochemical investigations of the latter were reported. The voltammetric studies of the complex revealed that it exhibits three one-electron reduction processes and a one-electron oxidation process. In situ spectroelectrochemical studies were performed to decide the origin of the redox processes which are assigned to (MnPc2-)-Pc-III/(MnPc2-)-Pc-II, (MnPc2-)-Pc-II/(MnPc2-)-Pc-I, (MnPc2-)-Pc-I/(MnPc3-)-Pc-I and (MnPc2-)-Pc-III/(MnPc1-)-Pc-III couples, respectively. The presence of oxygen significantly affected the in situ spectroelectrochemical behavior of the complexes due to the formation of mu-oxo MnPc species. An in situ electrocolorimetric method, based on the 1931 CIE (Commission Internationale de l'Eclairage) system of colorimetry, was applied to investigate the color of the electrogenerated anionic and cationic forms of the complex, which shows solvatochromic properties of the complex in solution. The possible polyelectrochromic application on solid state was suggested due to the color changes from brown to greenish blue and from brown to light yellow of a MnPc-coated thin film on ITO.
Keywords: TRANSITION-METAL PHTHALOCYANINES; SELF-ASSEMBLED MONOLAYER; LANGMUIR-BLODGETT-FILMS; MANGANESE PHTHALOCYANINE; PENTAFLUOROBENZYLOXY-SUBSTITUENTS; ELECTROCHEMICAL CHARACTERIZATION; ELECTROCATALYTIC BEHAVIOR; REVERSIBLE OXIDATION; MOLECULAR-OXYGEN; COMPLEXES